The missing half of the subduction factory: shipboard results from the Izu rear arc, IODP Expedition 350. Issue 13 (3rd October 2017) - Busby, Cathy J.; Tamura, Yoshihiko; Blum, Peter; Guèrin, Gilles; Andrews, Graham D. M.; Barker, Abigail K.; Berger, Julien L. R.; Bongiolo, Everton M.; Bordiga, Manuela; DeBari, Susan M.; Gill, James B.; Hamelin, Cedric; et al.
ABSTRACT: IODP Expedition 350 was the first to be drilled in the rear part of the Izu-Bonin, although several sites had been drilled in the arc axis to fore-arc region; the scientific objective was to understand the evolution of the Izu rear arc, by drilling a deep-water volcaniclastic section with a long temporal record (Site U1437). The Izu rear arc is dominated by a series of basaltic to dacitic seamount chains up to ~100-km long roughly perpendicular to the arc front. Dredge samples from these are geochemically distinct from arc front rocks, and drilling was undertaken to understand this arc asymmetry. Site U1437 lies in an ~20-km-wide basin between two rear arc seamount chains, ~90-km west of the arc front, and was drilled to 1804 m below the sea floor (mbsf) with excellent recovery. We expected to drill a volcaniclastic apron, but the section is much more mud-rich than expected (~60%), and the remaining fraction of the section is much finer-grained than predicted from its position within the Izu arc, composed half of ashes/tuffs, and half of lapilli tuffs of fine grain size (clasts <3 cm). Volcanic blocks (>6.4 cm) are only sparsely scattered through the lowermost 25% of the section, and only one igneous unit was encountered, a rhyolite peperite intrusion at ~1390 mbsf. The lowest biostratigaphic datum is at 867 mbsf (~6.5 Ma), the lowest palaeomagnetic datum is at ~1300 mbsf (~9 Ma), and the rhyolite peperite at ~1390 mbsf has yielded a U–Pb zircon concordia intercept age of (13.6 + 1.6/−1.7) Ma. Both arc front and rear arc sources contributed to the fine-grained (distal) tephras of the upper 1320 m, but the coarse-grained (proximal) volcaniclastics in the lowest 25% of the section are geochemically similar to the arc front, suggesting arc asymmetry is not recorded in rocks older than ~13 Ma.